Fatal poisoning in drug addicts in the Nordic countries in 2012. (March 2015) - Simonsen, K. Wiese; Edvardsen, H.M.E.; Thelander, G.; Ojanperä, I.; Thordardottir, S.; Andersen, L.V.; Kriikku, P.; Vindenes, V.; Christoffersen, D.; Delaveris, G.J.M.; Frost, J.
Highlights: We analysed data on fatal poisoning in drug addicts in 2012 from five Nordic countries. Differences in death rate among fatal poisoned drug addicts diminished between the countries compared to earlier studies. Opioids were the main cause of death among fatal poisoned drug addicts in all countries. Medicinal opioids had mainly replaced heroin/morphine. New psychoactive substances emerged. Abstract: This report is a follow-up to a study on fatal poisoning in drug addicts conducted in 2012 by a Nordic working group. Here we analyse data from the five Nordic countries: Denmark, Finland, Iceland, Norway and Sweden. Data on sex, number of deaths, places of death, age, main intoxicants and other drugs detected in the blood were recorded. National data are presented and compared between the Nordic countries and with data from similar studies conducted in 1991, 1997, 2002 and 2007. The death rates (number of deaths per 100, 000 inhabitants) increased in drug addicts in Finland, Iceland and Sweden but decreased in Norway compared to the rates in earlier studies. The death rate was stable in Denmark from 1991 to 2012. The death rate remained highest in Norway (5.79) followed by Denmark (5.19) and Iceland (5.16). The differences between the countries diminished compared to earlier studies, with death rates in Finland (4.61) and Sweden (4.17) approaching the levels in the other countries. Women accounted for 15–27% of the fatal poisonings. The median age of the deceased drug addicts was still highest in Denmark, and deaths of addicts >45 years old increased in all countries. Opioids remained the main cause of death, but medicinal opioids like methadone, buprenorphine, fentanyl and tramadol mainly replaced heroin. Methadone was the main intoxicant in Denmark and Sweden, whereas heroin/morphine caused the most deaths in Norway. Finland differed from the other Nordic countries in that buprenorphine was the main intoxicant with only a few heroin/morphine and methadone deaths. Deaths from methadone, buprenorphine and fentanyl increased immensely in Sweden compared to 2007. Poly-drug use was widespread in all countries. The median number of drugs per case varied from 4 to 5. Heroin/morphine, medicinal opioids, cocaine, amphetamines, benzodiazepines and alcohol were the main abused drugs. However, less widely used drugs, like gamma-hydroxybutyric acid (GHB), methylphenidate, fentanyl and pregabalin, appeared in all countries. New psychotropic substances emerged in all countries, with the largest selection, including MDPV, alpha-PVP and 5-IT, seen in Finland and Sweden.